Gender Differences in Involuntary Job Loss: Why are Men More Likely to Lose Their Jobs? - Wilkins, Roger; Wooden, Mark; Wilkins, R; Wooden, M (My University, 2013)
Empirical studies have consistently reported that rates of involuntary job loss are significantly lower among female employees than among males. Only rarely, however, have the reasons for this differential been the subject of detailed investigation. In this article, household panel survey data from Australia are used that also find higher rates of job loss among men than among women. This differential, however, largely disappears once controls for industry and occupation are included. These findings suggest that the observed gender differential primarily reflects systematic differences in the types of jobs into which men and women select.
Keywords: Employment -- Unemployment; Employment -- Labour force status and attachment; Gender -- Gender differences; Gender; Labour market; Gender; Employment; Labour force status and attachment; Unemployment; Gender differences; Gender; Employment and unemployment